Upaya Meningkatkan Motivasi Belajar Sepak Bola Melalui Video Pembelajaran Berbasis Canva : Pendekatan Inovatif - Glennada Risty; Fathurahman Fathurahman; Ganang Gutamara; Sigra Santika Satria Dhani; Abdul Rachman Syam (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to evaluate the effect of using Canva media on students' motivation and learning outcomes, especially in soccer material. The method used is a quantitative approach with a One Group Pretest-Posttest experimental design. The subjects of the study consisted of 59 ninth grade students of SMP Labschool Unesa 3 Surabaya, with a sample of 20 students from class IX-A. Data were collected through a questionnaire and pretest and posttest were conducted. Data analysis included normality, homogeneity, and hypothesis testing. The results showed an average pretest score of 84.68 and a posttest of 63.10, with an increase in learning motivation of 92.41. The average learning outcome before the intervention was 4.1765, while after it became 6.0588. The T-test showed a significance value (2-tailed) of 0.000 ≤ 0.005, so the alternative hypothesis was accepted and the null hypothesis was rejected. This indicates that Canva media contributes positively to increasing student motivation and learning outcomes in soccer learning, as seen from the increasing enthusiasm of students during the learning process.